2000
DOI: 10.3109/02770900009055474
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Skin Test Reactivity, Total Serum IgE Levels, and Peripheral Blood Eosinophilia with Asthma in Kuwait

Abstract: There is evidence that elevated serum immunoglobulin E (IgE) and eosinophilia correlate well with allergic skin test reactivity. These parameters have been used as alternative methods to characterize atopic subjects. Skin test reactivity is the only measure used routinely in clinical practice in Kuwait to reflect atopy in asthma patients. This study examines the usefulness of the two other parameters of atopy in patients with asthma, and to determine the most common allergens involved in Kuwait. Between 1998 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Khadadah et al . [42] in their study reported positive correlation between total blood eosinophil counts, serum total IgE levels, and eosinophilic cationic protein.…”
Section: Discussionmentioning
confidence: 97%
“…Khadadah et al . [42] in their study reported positive correlation between total blood eosinophil counts, serum total IgE levels, and eosinophilic cationic protein.…”
Section: Discussionmentioning
confidence: 97%
“…37 Previous studies among children with asthma in Kuwait have also shown a broadly similar sensitization rate to dust mite compared with the current study. 22,38 Interestingly, a study conducted in Kuwait 2 decades ago reported a much lower rate of sensitization to dust mite (1.5%). 39 Thus, comparing our data with those available from Kuwait 20 to 25 years ago, it would appear that the prevalence of both asthma and sensitization rates have increased dramatically.…”
Section: Discussionmentioning
confidence: 96%
“…In a study, a positive correlation between serum total IgE levels, total blood eosinophil counts and eosinophil cationic protein (ECP) was reported. (25) Eosinophils play an important role in the pathogenesis of asthma. Airway inflammation, involving infiltration of the bronchial wall by activated eosinophils, mast cells and T lymphocytes, is an established feature of asthma.…”
Section: Resultsmentioning
confidence: 99%